2020
DOI: 10.1186/s12884-020-02908-w
|View full text |Cite
|
Sign up to set email alerts
|

Twin pregnancies with uterine fibroids are not at increased risk for obstetric complications: single center cohort study

Abstract: Background: Twin pregnancies with uterine fibroid(s) (UFs) may not be at increased risk for obstetric complications compared to those without UFs. However, there was no reported comparison study with obstetric outcomes and complications of twin pregnancy after myomectomy. We aimed to compare the pregnancy outcomes in twin pregnancies with or without uterine fibroid(s), and also compared in patients with previous myomectomy history in Korean women. Methods: A cohort of twin pregnancies delivered in a single ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, the effects of uterine fibroids on the risk of PPH after CD remain poorly understood. Some studies reported that uterine fibroids do not increase the risk of obstetric complications 49 , 50 . In contrast, other studies found that uterine fibroids with a diameter of over 5 cm are a risk factor for PPH after CD 30 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of uterine fibroids on the risk of PPH after CD remain poorly understood. Some studies reported that uterine fibroids do not increase the risk of obstetric complications 49 , 50 . In contrast, other studies found that uterine fibroids with a diameter of over 5 cm are a risk factor for PPH after CD 30 , 51 .…”
Section: Discussionmentioning
confidence: 99%